The effect of etching solution on adsorption properties of Ti3CNTx for chlortetracycline removal - Hanay, Ozge; Celik, Aytekin; Aksoy, Yunus; Halisdemir, Umay; Hasar, Halil (Royal Soc Chemistry, 2025)
2D MXenes are highly promising for adsorption due to their hydrophilicity, large surface area, multilayer structure, and surface functionalities. This study synthesizes a new MXene, titanium carbonitride (Ti3CNTx), using HF and LiF + HCl etching solutions, resulting in two types: M-HF30 and M-LiF + HCl. The adsorption capacities of these MXenes were evaluated for chlortetracycline hydrochloride (CTC). Characterization techniques, including X-ray powder diffraction, scanning electron microscopy, the pH of the point of zero charge, and Fourier-transform infrared spectroscopy were employed to assess the material properties and structural changes post-CTC contact. Both MXenes demonstrated significant CTC adsorption, with M-LiF + HCl achieving a higher removal capacity of 290 mg g-1 compared to 105 mg g-1 for M-HF30. This enhanced performance is attributed to LiF intercalation and improved surface functional groups, even if it has a lower surface area than M-HF30. Adsorption kinetics and isotherms indicated that CTC adsorption followed a pseudo-second-order kinetic model and the Langmuir model, suggesting monolayer adsorption dominated by chemisorption. Additionally, M-LiF + HCl showed good reusability over three adsorption cycles. Overall, Ti3CNTx MXene, particularly M-LiF + HCl, presents a promising new adsorbent for water treatment applications.
Keywords: Ti3C2Tx Mxene Nanosheets; Aqueous-Solution; Antibiotics